The Humanist Ulrich von Hutten A Reappraisal of his Humor - Best, Thomas W. (UNC Studies in the Germanic Languages and Literatures, 1969)
Ulrich von Hutten (1488-1523), Renaissance-Reformation publisher and ardent champion of German nationalism, has previously been characterized as a bitter and vehement political satirist. From this concise, critical survey of his comic writing a more balanced, congenial image of Hutten emerges.